Implementasi Sistem Informasi Akuntansi atas Pengakuan Pendapatan pada Perusahaan Asuransi Syariah: Studi Kasus PT Asuransi Jasindo Syariah dan PT Asuransi Syariah XYZ - Pratiwi, Almas Yusnan; Wibowo, Daryanto Hesti (Institut Ilmu Sosial dan Manajemen Stiami, 2024)
Statement of Financial Accounting Standard (PSAK) 108 regulates Islamic insurance transactions in Indonesia, including revenue recognition. This study aims to determine how the implementation of revenue recognition information system in Islamic insurance companies. This research applies descriptive research with a qualitative approach, namely the presentation of data in the form of descriptive and objective. The object of this research is the implementation of revenue recognition accounting information system in sharia insurance companies in 2020 at PT Asuransi Jasindo Syariah and PT Asuransi Syariah XYZ. The results of this study indicate that PT Asuransi Jasindo Syariah and PT Asuransi Syariah XYZ do not recognize participant contributions as revenue, but the contribution funds will go into the tabarru' fund. The ujrah fee received for this tabarru' fund is then recognized as revenue. It can be concluded that PT Asuransi Jasindo Syariah and PT Asuransi Syariah XYZ have both carried out the implementation of the revenue recognition accounting information system properly, in accordance with PSAK 108. The implication of this research is to see the extent to which Islamic insurance companies in Indonesia apply PSAK 108 to revenue recognition.